Basics of Statistics for Clinical Research in Hand Surgery - Rosales, Roberto S.; Atroshi, Isam (Revista Iberoamericana de Cirugía de la Mano, 2018)
Statistics, the science of numerical evaluation, helps in determining the real value of a hand surgical intervention. Clinical research in hand surgery cannot improve without considering the application of the most appropriate statistical procedures. The purpose of the present paper is to approach the basics of data analysis using a database of carpal tunnel syndrome (CTS) to understand the data matrix, the generation of variables, the descriptive statistics, the most appropriate statistical tests based on how data were collected, the parameter estimation (inference statistics) with p-value or confidence interval, and, finally, the important concept of generalized linear models (GLMs) or regression analysis.
Keywords: clinical research; statistic; carpal tunnel syndrome; methodology; hand